Surveilling brain damage using brain biomarkers in hypoglycemic neonatal calves with diarrhea - Ider, Merve; Naseri, Amir; Ok, Mahmut; Erturk, Alper; Durgut, Murat Kaan; Iyigun, Suleyman Serhat (Frontiers in Veterinary Science, 2023)
Hypoglycemia is a condition associated with neonatal diarrhea in calves, leading to increased mortality and neurological clinical signs. The aim of the present study was to determine the development of brain damage in hypoglycemic calves with neonatal diarrhea and the diagnostic and prognostic significance of these biomarkers. Ten healthy and 50 hypoglycemic calves with diarrhea were included in the study. Clinical examination, blood gases and complete blood count were performed at admission. Blood serum calcium-binding protein B (S100B), neuron-specific enolase (NSE), glial fibrillary acidic protein (GFAP), ubiquitin carboxyl-terminal hydrolysis isoenzyme-1 (UCHL-1), activitin A (ACT), adrenomodullin (AM) concentrations, and creatine kinase-BB (CK-BB) enzyme activity were measured using commercial bovine-specific ELISA kits to assess brain damage. Of the hypoglycemic calves enrolled in the study, 13 (26%) survived and 37 (74%) died. In addition, 32 (64%) of the calves had severe acidosis and 24 (48%) had sepsis. S100B, GFAP, UCHL-1, CK-BB (p < 0.001) and NSE (p < 0.05) concentrations were significantly higher in hypoglycemic calves compared to healthy calves, while ACT concentrations were lower. Blood glucose concentration was negatively correlated with serum S100B, GFAP, UCHL-1 and CK-BB enzyme activity and positively correlated with ACT in hypoglycemic calves (p < 0.01). Brain injury biomarkers were not predictive of mortality (p > 0.05). Morever, severe hypoglycemia, severe acidosisemia and sepsis variables were not found to have sufficient capacity to predict mortality when considered alone or together (p > 0.05). In conclusion, brain damage may develop as a consequence of hypoglycemia in calves and increase mortality risk. S100B, NSE, GFAP, UCHL-1, ACT and CK-BB concentrations can be used to diagnose brain damage in hypoglycemic calves. However, the variables of severe hypoglycemia, severe acidosisemia, and sepsis together with the biomarkers of brain injury have a limited value in predicting the prognosis of neonatal calves with diarrhea.